Questioning Practices in Indonesian English Language Classrooms: An Analysis of Question Types and Student Engagement - Putri, Preti Precillia; Rasuki, Muhlisin; Astutik, Indri (English Education Program, Education Faculty, Universitas Nurul Huda, 2024)
This study examines the question types used by Indonesian English language teachers in high school classrooms and their impact on student engagement. The data were derived from two YouTube videos showcasing English language teaching in real classroom contexts. The questions posed by the teachers during the English language lessons were coded according to two criteria: convergent and divergent questions. Student engagement is measured by the number of responses to the teachers’ questions. The results reveal that the predominant type of questions used by the teachers during the lessons were convergent questions, which seek specific information or recall from students, while divergent questions, which encourage open-ended and varied responses, were used much less frequently. Furthermore, student engagement remained limited across both question types, with only a few students participating in responding. These findings highlight the prevalence of a traditional instructional approach characterized by convergent questions. The article concludes with some suggestions for utilizing alternative instructional interventions that can promote more interactive questioning practices and potentially enhance student engagement during English language instruction.